PKM Guru TK Dalam Upaya Optimalisasi Perkembangan Motorik Kasar Pada Anak Usia 4-6 Tahun Dengan Pemberian Stimulasi Brain Gym Di KB TK Islam Sultan Agung 02 Kota Semarang Jawa Tengah - Fitratun Najizah; Shella Dhika R.; Rafif Aydin Maheswara; Cintya Putri Anisah; Fiantika Aprianingrum; Friesca Persityara Agatha; Naufal Adib Ramadhani (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The pre-school period is a golden age where stimulation of all aspects of development plays an important role in subsequent developmental tasks, where 80% of children's cognitive development has been achieved at pre-school age. In general, learning for children aged 4-6 years for aspects of physical or motor development is more focused on fine motor skills. Meanwhile, gross motor skills receive less attention. Gross motor development is as important as other aspects of development, because a child's inability to carry out physical activities will give rise to a negative self-concept in the child. WHO reports that 5-25% of pre-school children suffer from minor brain dysfunction including gross motor development disorders that zero point four 8 million (16%) toddlers in Indonesia experience developmental disorders both gross and fine motor development, hearing loss, intelligence lack and delay in speaking. Eighty-five thousand seven hundred and seventy-nine (62.02%) pre-school age children experience developmental disorders. Based on research related to the brain gym method, children who like to move and play actively tend to develop their brain nerves more rapidly. This brain gym method is very helpful in moving body parts, coordinating movements, helping skills in learning at school and in guiding adjustments to daily activities. The PKM STIKES Kesdam IV/Diponegoro Semarang team plans to provide community service, especially to the students of KB-TK Islam Sultan Agung 02 Semarang regarding efforts to optimize motor development using the brain gym method. This service will be carried out in partnership with the Sultan Agung Education Foundation, Semarang City. The distance between the activity location and STIKES Kesdam IV/Diponegoro Semarang is approximately ± 10km. This service activity method is carried out in several stages, starting from observation, socialization with parents to establishing collaboration with teaching teachers. The proposed budget and schedule for implementing community service are very relevant or in accordance with the activities to be carried out.